PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP OPINI AUDIT GOING CONCERN MELALUI KUALITAS AUDIT (STUDI EMPIRIS PADA KANTOR AKUTAN PUBLIK DI JAWA TIMUR) - ONIZ ULFA PERMATA; SUTRISNO SUTRISNO; IMAM SUBEKTI (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Abtract This study examined the effect of the competence and independence of the auditor's going-concern opinions through quality audits. Tests conducted on 109 auditors who worked on the public accounting firm in East Java. Proxied competence level of education, training and experience, and professional education, while independence is proxied relationships with clients, the pressure from the client, the amount of non-audit services and feesThe results showed the level of education, training and experience, professional education, relationships with clients and pressure from clients positive influence going concern audit opinion, while the non-audit services and the amount of the fee has no effect. The level of education, training and experience, the pressure from clients and non-audit services positive effect on audit quality, while professional education, relationships with clients and the amount of the fee has no effect. The results also showed a positive effect on the quality of audit opinions going concern, but it can only mediate audit quality education, training and experience, and the pressure from the client to the going-concern audit opinion. Based on these results it can be concluded that the competence, independence and audit quality is a determinant of the going concern opinions. Keywords: Competence auditor, auditor independence, audit quality, going concern opinions.